Validation of a reference gene for transcript analysis in cassava (Manihot esculenta Crantz) and its application in analysis of linamarase and α-hydroxynitrile lyase expression at different growth stages - Sukhuman Whankaew (2016)
Relative real-time reverse transcription quantitative polymerase chain reaction (RT-qPCR) is a well-established method for the precise quantification of gene expression. For accurate relative real-time RT-qPCR analysis, validation of the expression of an appropriate reference gene is required. In this study, the expression of six commonly used reference genes, namely 40S ribosomal protein (40S), actin (ACT), cyclophilin C (CYCC), EF-1 alpha (EF1), TATA box binding protein (TBP) and polyubiquitin (UBI) was investigated in leaf and root samples of cassava obtained at 6, 9 and 12 months after planting (MAP). A transcript stability analysis was undertaken in two different varieties of cassava, namely Huay Bong 60 which has high cyanogenic potential (CN) and Hanatee which has low CN. The results reveal that TBP was the most stable reference gene for expression studies. This information was applied to an analysis of linamarase and α-hydroxynitrile lyase gene expression in samples from six low and six high CN cassava plants collected at 6, 9 and 12 MAP. The results indicate that at 6 MAP, the linamarase transcript from leaf of the high CN group was significantly increased, and the α-hydroxynitrile lyase transcript was significantly increased at 12 MAP.